The validity of clinical examination in screening of developmental dysplasia of the hip among infants aged less than six months - Dalal Ihsan Alswari; Selwa Elias Yacoub; Rajab Hassan Sanaan (Advanced Medical Journal)
Background and objectives:Developmental dysplasia of the hip is a challenging condition, requiring screening for ear- ly diagnosis. This study was conducted to assess the validity of clinical screening tests of developmental dysplasia of the hip among infants aged less than 6 months.